Allergia da animali da laboratorio / Laboratory animal allergy - Corradi, M.; Romano, C.; Mutti, A. (La Medicina del Lavoro, 2011)
Summary «Laboratory animal allergy». Laboratory animal allergy (LAA) may develop when susceptible persons are exposed to allergens produced by laboratory animals. LAA is associated with exposure to urine, fur, and salivae of rats, mice, guinea pigs, dogs and rabbits. Approximately 30% of persons who are exposed to laboratory animals may develop LAA and some will also develop asthma. LAA is most likely to occur in persons with previously known allergies, especially to domestic pets. The majority of LAA sufferers experience symptoms within six months their first exposure to laboratory animals; almost all develop symptoms within three years. The most common symptoms are watery eyes and an itchy, runny nose, although skin symptoms and lower respiratory tract symptoms may also occur. Feeding and handling laboratory animals or cleaning their cages generates ten times the amount of allergens compared with undisturbed conditions. Prevention of animal allergy depends on control of allergenic material in the work environment and on organizational and individual protection measures. Pre-placement evaluation and periodic medical surveillance of workers are important pieces of the overall occupational health programme. The emphasis of these medical evaluations should be on counselling and early disease detection.